BEST PRACTICE CONSTRUCTION OF HOUSE OF WORSHIP BASED ON LOCAL WISDOM IN PALU - Muhammad Dachlan (Al-Qalam, 2021)
The construction of houses of worship is often rejected in some regions of Indonesia. This phenomenon also occurs in Palu City. This article aims to find out how to build a house of worship based on local wisdom in Palu. By using qualitative methods, the following research results were obtained. First, the best practice of religious harmony was reflected in multicultural education, religious harmony, and cooperation in social practice. Second, the values of local wisdom that become a social tool are the culture of sintuvu (cooperation), nasorara nosabatutu (brotherhood), nasobolai (openness), libu ntodea (agreement), tonda talosi (harmony). Besides, houses of worship were also built with architectural designs with local wisdom. Third, the government's role in creating best practice of inter-religious harmony can be seen through the existence of FKUB, which has excellent programs, such as unspoiled faith for harmony, village harmony, harmony sermons, and technical guidance for traditional stakeholders.